2022
DOI: 10.1155/2022/4685642
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Potential Health Risk of Gold Nanoparticles Used in Nanomedicine

Abstract: Due to unique properties, nanoparticles (NPs) have become a preferred material in biomedicine. The benefits of their use are indisputable, but their safety and potential toxicity are becoming more and more important. Especially, excessive production of reactive oxygen species (ROS) induced by the strong oxidation potential of metal NPs could evoke adverse effects associated with damage to nucleic acids, proteins and lipids. Our study gives a view on the potential cytotoxicity of gold NPs (Au NPs) of different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…GSH levels decreased in both cell lines, indicating an increase in the production of reactive oxygen species, contributing to the cytotoxicity. Gold nanoparticles may cause oxidative stress and damage to biological molecules due to changes in antioxidant enzyme activities in healthy (HEK 293 T) and cancer (A375 and A594) cell lines, as shown in a study by Dvorakova et al [166]. In another study conducted by Bin-Jumah et al [162], cytotoxicity of AuNPs was dose-dependent, confirmed by two methods in two cell lines-CHANG (normal) and HuH-7 (liver cancer).…”
Section: Mechanism Related To Oxidative Stressmentioning
confidence: 75%
“…GSH levels decreased in both cell lines, indicating an increase in the production of reactive oxygen species, contributing to the cytotoxicity. Gold nanoparticles may cause oxidative stress and damage to biological molecules due to changes in antioxidant enzyme activities in healthy (HEK 293 T) and cancer (A375 and A594) cell lines, as shown in a study by Dvorakova et al [166]. In another study conducted by Bin-Jumah et al [162], cytotoxicity of AuNPs was dose-dependent, confirmed by two methods in two cell lines-CHANG (normal) and HuH-7 (liver cancer).…”
Section: Mechanism Related To Oxidative Stressmentioning
confidence: 75%